PPP1R3G–RIPK1–ZBP1 axis activates early-stage apoptosis and late-stage necroptosis to promote doxorubicin-induced cardiotoxicity - Xueling Ma; Ken Chen; Zhigao Wang (Proceedings of the National Academy of Sciences, 2026)
Cardiotoxicity is a dose-limiting complication of doxorubicin (DOX) chemotherapy, yet the molecular mechanisms governing the transition from acute stress to terminal heart failure remain incompletely defined. Here, we identify Protein Phosphatase 1 Regulatory Subunit 3G (PPP1R3G) as a central regulator of a RIPK1–ZBP1 signaling axis that drives DOX-induced cardiotoxicity. We demonstrate that DOX initiates a biphasic death program. Initially, DOX triggers p38-mediated inhibitory phosphorylation of RIPK1, which functions as a transient molecular “brake” against cell death. However, sustained stress recruits PPP1R3G to dephosphorylate RIPK1, “unleashing” its activity and triggering early-stage apoptosis. Activated RIPK1 subsequently promotes the cytosolic release of mitochondrial DNA (mtDNA), which induces Z-DNA-binding protein 1 (ZBP1) expression via an IFN-β signaling circuit. This establishes a lethal feed-forward loop where ZBP1 senses mtDNA to amplify late-stage necroptosis. Genetic ablation of Ppp1r3g in mice significantly suppresses both apoptosis and necroptosis, attenuates systemic inflammatory cytokine production (TNFα, IFN-β, and IFN-γ), and provides robust protection against DOX-induced cardiac dysfunction and mortality. Our findings delineate the PPP1R3G–RIPK1–ZBP1 axis as the central relay converting a protective phosphorylation checkpoint into a sustained death program. These results identify PPP1R3G as a critical gatekeeper of cardiac viability and a promising therapeutic target for mitigating chemotherapy-induced cardiotoxicity.